PERAN BAZNAS KOTA BANJARMASIN DALAM PENGEMBANGAN USAHA MIKRO (Pendekatan Studi Kasus) - Muhammad Ma'ruf Abdullah; Sri Anafarhanah; Elida Mahriani (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
Poverty is a multidimensional problem that is faced by many developing countries. Poverty in Indonesia is caused by many factors such as limitation of physical, psychological resources,and economic access. According to Yusuf Qaradawi, to overcome poverty, charity is the first goal and become the main purpose of zakat. This study tried to assess the impact of zakat in alleviating poverty and making zakat as a productive source for the development of micro-enterprises that are expected to realize the main purpose of the charity which is the welfare of society. This research is a case study using a sample of “Ovi” Laundry business as one of the businesses that are considered capable of evolving with ZIS funds provided by BAZNAS city of Banjarmasin. These results indicate that internal factors (accuracy in planning, careful in spending, consequence of developing the business, intention to be independent, and regular cash flow) and external factors (capital loan of BAZNAS) greatly affects the performance of the business and business continuity of Ovi Laundry. The success of this effort demonstrated by the indicators is perceived and recognized by the owner who is able to pay for everyday household, the education of her children and save for the future.